Process Management In The Leasing Sector (Research Bulletins of the Faculty of Economic Sciences, 2017)
The main aim of this article is to present the use of the concept of process management to define the processes in the leasing company. For this purpose also there was presented the leasing sector in Poland, its characteristics. Moreover, in the article are presented the main processes and supporting processes orienting the company's strategy on the quality of customer service, especially customer who decides to establish a relationship with the leasing company.
Keywords: process management; leasing; leasing company; customer service; quality